Characterization and optimization of CdZnTe Frisch collar gamma-ray spectrometers and their development in an array of detectors - Kargar, Alireza (Kansas State University, 2009)
Cadmium Zinc Telluride (CdZnTe) has been used for many applications, such as medical imaging and astrophysics, since its first demonstration as a room temperature operating gamma-ray detector in 1992. The wide band gap, high effective Z-number and high resistivity of CdZnTe make it a good candidate for use as a room temperature operated detector with good absorption efficiency, while maintaining a low bulk leakage current at high electric fields. Nevertheless, the low mobility lifetime products mu tau of holes in CdZnTe makes detectors position sensitive, unless advanced detector designs are employed. Among those designs is the Frisch collar technology which turns the detector into a single carrier device by negating the degrading effects of hole trapping and low mobility. The superiority of the Frisch collar technology over other methods include its inexpensive associated electronics and straight forward fabrication process. The main objective of this research study is to develop a large volume gamma-ray detector with an array of individual CdZnTe Frisch collar gamma-ray spectrometers while still using a single readout. Several goals were to be accomplished prior to the main objective. One goal is to develop a reliable low cost method to fabricate bulk CdZnTe crystals into Frisch collar detectors. Another goal was to investigate the limitations of crystal geometry and the crystal electrical properties to obtain the best spectroscopic performance from CdZnTe Frisch collar detectors. Still another goal was to study all other external parameters such as the collar length, anode to cathode ratio, the insulator thickness and applied voltage on performance of CdZnTe Frisch collar detectors. The final goal was to construct the CdZnTe Frisch collar devices into an array and to show its feasibility of being used for large volume detector.
Keywords: CdZnTe; Frisch; Gamma-ray; Detector; Spectrometer; Cadmium Zinc Telluride; CZT; Engineering, Nuclear (0552)